A Escola Normal Regional Nossa Senhora do Carmo em Belo Jardim-PE: desfilando o habitus professoral pelas ruas da cidade. - Sousa., Bernardina Santos Araújo de (2013)
It is evident the effective participation of the catholic segment in the new directions of the town, including in it the public instruction. In this sense, the crossway of the catholic morality and the teachers‟ education proposal is unveiled as teacher s habitus. Habitus, as a category, is borrowed from Pierre Bourdieu and particularized, in the educational perspective, as a manifestation of a way to be a teacher. Michel de Certeau contributes with the category of quotidian. Through it, the explicit marks of way of being a school and the way of being a city is explored. The categories of memory, silence and forgetfulness find in Paul Ricoeur a fundamental theoretical support. These categories recover along the text some important references about the collective memory of the normalistas‟ (teachers to be in the process of education), of the town and of the Escola Normal Regional Nossa Senhora do Carmo‟. The 1950 decade situates temporally this research as this period refers to the implantation and the closure of this institution. Belo Jardim, Pernambuco responds for the space where this institution wrote its existence. The narratives, the written and iconographic documents, and the journals constituted the corpus of the research. Being ethnographic, this research involves eight subjects in interviews. Seven of them used to be students and one used to be a teacher at the Escola Normal‟. The personal files, as well as the interviewers‟ biographical objects contributed significantly to the constructed understandings about the research object. In the same way, the public achieves contributed with their documents and journals to elucidate various points along this study. The consociated projects referred in the objective supported the commitment of the teacher‟s education with a model of society that assumed the contents of the civilization, higienism, and modernization as the proposed horizon. Thus, the so called the fine flowers girls were demanded, as subjects of prestige, to be committed to the construction of a town in quest of a urban model, designed upon the economical perspective of the industrial capital. This perspective, for one hand, demands a paradigm of the higienism, civilization, urbanity and patriotism and, for another, must preserves the patterns of the catholic morality. In consequence, these women were introduced in this model, as protagonists in the search of the balance between the tensions keeping apart and putting together new habits and old catholic traditions. The genealogy of the Escola Normal Regional Nossa Senhora do Carmo‟ reveals the teachers Antenor Vieira de Melo and Maria do Carmo Paes Vieira as the ones who fomented, in the local plots, the installation of both the Instituto São Luiz e da Escola Normal Regional Nossa Senhora do Carmo. In this sense, they were the responsible ones for the symbolic construction of this paradigm. The religious and civic festivals are highlighted as being of equivalent value to the consociated projects guiding the proposed urban model. The strong involvement of the Escola Normal‟ in these festivals, in spite of its private non-confessional nature, reveals the intents of a town building its conservative-modern discourse through the teacher‟s education bias. Thus, the Escola Normal‟ was identified, by the way of the establishment and consolidation of the teacher s habitus, as the proper ambience to prepare, in the missionary view, the new protagonists of the proposed urban reformation.